Recent Publications upon Economics (Quarterly Journal of Economics, 1897)
Journal Article Recent Publications upon Economics Get access The Quarterly Journal of Economics, Volume 12, Issue 1, October 1897, Pages 99–104, https://doi.org/10.1093/qje/12.1.99 Published: 01 October 1897